Implementing and developing secure low-cost long-range system using speech signal processing - Samer Alabed; Amer Alsaraira; Nour Mostafa; Mohammad Al-Rabayah; Yehia Kotb; Omar A. Saraereh (Institute of Advanced Engineering and Science, 2023)
In the proposed work, we present a secure low-cost speech communication system for long-distance communication. The system utilizes long range (LoRa) technology to transmit speech signals. LoRa technology uses spread-spectrum modulation to enable long-range communication with low power consumption. LoRa modulation allows for data transfer at a slow speed, typically below 22 kbps, which makes it infeasible for transmitting speech. To address this limitation, we suggest a speech coding technique that reduces the overall data rate of speech signals to below 7.5 kbps. This lower rate is more compatible with the LoRa module and ideal for transmitting speech. Moreover, this technique can improve the LoRa transmission range. Additionally, we have developed an encryption-decryption method to ensure the privacy of the messages and prevent unauthorized access by third parties.